O Enigma do Mal: uma leitura do 'De casu diaboli'de Santo Anselmo (The enigma of evil: a reading of St. Anselm’s De casu diaboli) - DOI: 10.5752/P.2175-5841.2013v11n32p1551 - Vasconcellos, Manoel Luís Cardoso (Horizonte, 2013)
This article aims to investigate the problem of evil in Saint Anselm, especially in his treatise De casu diaboli. He approaches this issue from the close connection between evil and sin. Upon analyzing evil from the diabolic fall perspective, Dr. Magnificent tries to establish a connection between will, freedom and justice. This text investigates the moral meaning of misconduct, carried out by a rational and purely spiritual creature that was created good and meant to be good. Seeking for happiness is not itself a sin, according to the author, for such a wish is a gift from God. The evil done by the angel lies in the act of wanting happiness without justice, that is, on wanting to be happy, the angel contradicted what he was supposed to be: he wanted to be like God, transcending his own nature, as he wished for something that, as a creature, he was not fit to wish for. This is the starting point to analyze evil and its most dramatic consequence: suffering.